Quantitative dose-response analysis of ethyl methanesulfonate genotoxicity in adult gpt-delta transgenic mice - Cao, Xuefei; Mittelstaedt, Roberta A.; Pearce, Mason G.; Allen, Bruce C.; Soeteman-Hernández, Lya G.; Johnson, George E.; Bigger, C. Anita H.; Heflich, Robert H. (Environmental and molecular mutagenesis, 2014)
The assumption that mutagens have linear dose–responses recently has been challenged. In particular, ethyl methanesulfonate (EMS), a DNA‐reactive mutagen and carcinogen, exhibited sublinear or thresholded dose‐responses for LacZ mutation in transgenic Muta™Mouse and for micronucleus (MN) frequency in CD1 mice (Gocke E and Müller L [2009]: Mutat Res 678:101–107). In order to explore variables in establishing genotoxicity dose–responses, we characterized the genotoxicity of EMS using gene mutation assays anticipated to have lower spontaneous mutant frequencies (MFs) than Muta™Mouse. Male gpt‐delta transgenic mice were treated daily for 28 days with 5 to 100 mg/kg EMS, and measurements were made on: (i) gpt MFs in liver, lung, bone marrow, kidney, small intestine, and spleen; and (ii) Pig‐a MFs in peripheral blood reticulocytes (RETs) and total red blood cells. MN induction also was measured in peripheral blood RETs. These data were used to calculate Points of Departure (PoDs) for the dose responses, i.e., no‐observed‐genotoxic‐effect‐levels (NOGELs), lower confidence limits of threshold effect levels (Td‐LCIs), and lower confidence limits of 10% benchmark response rates (BMDL10s). Similar PoDs were calculated from the published EMS dose–responses for LacZ mutation and CD1 MN induction. Vehicle control gpt and Pig‐a MFs were 13–40‐fold lower than published vehicle control LacZ MFs. In general, the EMS genotoxicity dose–responses in gpt‐delta mice had lower PoDs than those calculated from the Muta™Mouse and CD1 mouse data. Our results indicate that the magnitude and possibly the shape of mutagenicity dose responses differ between in vivo models, with lower PoDs generally detected by gene mutation assays with lower backgrounds. Environ. Mol. Mutagen. 55:385–399, 2014. © 2014 Wiley Periodicals, Inc.